2018
DOI: 10.1177/0049475518786854
|View full text |Cite
|
Sign up to set email alerts
|

How healthy are children one year after discharge from nutritional rehabilitation centres?

Abstract: Nutritional rehabilitation centres (NRCs) have been established to ensure the nutritional recovery of severely malnourished children. The long-term nutritional outcomes in children discharged from NRCs have not been described. In this retrospective cohort study, the nutritional status of 514 children was assessed one year after discharge. Household and maternal data, as well as data regarding variables related to the children's stay at the NRC, were collected. A total of 33.4% had moderate malnutrition and 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A recent systematic review found that the strongest and most consistent risk factor for relapse after SAM treatment in CMAM programs is low anthropometric measurements at admission [24]. Another study in India reported that children with a MUAC under 105 mm at admission had a 6.46 times increased risk of SAM a year after discharge, although they did not find any significant association with a low WHZ [25]. Various studies have found evidence that high severity at admission is associated with an increased risk of death after discharge.…”
Section: Discussionmentioning
confidence: 98%
“…A recent systematic review found that the strongest and most consistent risk factor for relapse after SAM treatment in CMAM programs is low anthropometric measurements at admission [24]. Another study in India reported that children with a MUAC under 105 mm at admission had a 6.46 times increased risk of SAM a year after discharge, although they did not find any significant association with a low WHZ [25]. Various studies have found evidence that high severity at admission is associated with an increased risk of death after discharge.…”
Section: Discussionmentioning
confidence: 98%